Mixed phenotype acute leukaemia: a case report of an unusual presentation - Gurusamy, Veeraraghavan; Panneerselvam, Ramya; Jayanthi, Bharathi Vidhya (International Journal of Research in Medical Sciences, 2017)
Mixed phenotype acute leukaemias (MPALs), a varied group of disorders pose a diagnostic challenge to the physicians and pathologists alike. This rare subset of acute leukaemias are characterised by the presence of blasts which express markers of more than one lineage (B-lymphoid / T-lymphoid / Myeloid lineage), making the essentiality of immunophenotyping more pertinent. MPALs are included in the acute leukaemias of ambiguous lineage under the World health organization (WHO) classification of tumours of haematopoietic and lymphoid tissues. We describe here a case report of mixed phenotype acute leukaemia (T-Lymphoid/Myeloid).